Dermaseptins, Multifunctional Antimicrobial Peptides: A Review of Their Pharmacology, Effectivity, Mechanism of Action, and Possible Future Directions - Bartels, Emiel Jacob Henri; Dekker, Douwe; Amiche, Mohamed (Frontiers in Pharmacology, 2019)
Peptides produced by animals could be an inspiration for biopharmaceutical drugs. Dermaseptins, multifunctional antimicrobial peptides, isolated from the Amazonian tree-frog of Phyllomedusa genus, are a group of α-helical shaped polycationic peptides that show effectivity in vitro against bacteria, parasites, protozoa, viruses and tumors and without effects on normal eukaryote cells. However, no clinical trials have been conducted thus far. This systematic review summarizes the current knowledge on the pharmacology, effectivity against infectious pathogens and tumors cells and the mechanism of action of the Dermaseptins. Gaps in this knowledge remain: a unifying mechanism of action, the effectivity of Dermaseptins against several cancer cell lines and safety in humans. Potential future applications include: antiseptic topical ointments, early interfering anti-viral medicine, anti-conceptive, anti-tumor agent and an alternative to plant pesticides through applied biotechnology.